دور النقابات العمالية في تحسين أداء العاملين (دراسة ميدانية عن نقابة عمال التبغ في دائرة جبلة) - ابراهيم حسين; طرابلسية شيراز; عبد الحميد فاطمة (Latakia University Journal - Economic and Legal Sciences Series, 2016)
performance of employees. The research aims to identify the reality of the work of tobacco workers union in Jablah Department, in order to stand on their success in protecting the interests and rights of members of workers, and to provide the necessary services to them, as well as to identify their role in improving the performance of workers in Jablah department. The researcher has prepared and distributed a questionnaire on the research sample, which amounted to (77) were distributed among workers (15) in the office of trade union members and (62) a member of the guild. Data were using SPSS statistical analysis software. The researcher found a set of results the most important was: . There is a strong and positive relationship between the work and the performance of the tobacco workers union, the more the union work to provide the necessary services as well that led to improved performance of the employees. . There is a statistically significant relationship between economic and recreational side of the reality of the work of the union and its role in improving the performance of employees. . There is no statistically significant relationship between the health aspect of the reality of the work of the union and its role in improving the performance of employees. . There is no statistically significant relationship between the ability of union members to influence the administration and improve the performance of employees. . There is a statistically significant relationship between the reality of the work of the union by the selection of members of the t تهدف الدراسة إلى التعرّف على واقع عمل نقابة عمال التبغ في دائرة جبلة بهدف الوقوف على مدى نجاحها في أداء دورها من حيث حماية مصالح وحقوق العمال الأعضاء فيها، وتقديم الخدمات الضرورية لهم وذلك من الجوانب الاقتصادية والترفيهية والصحية، بالإضافة إلى التعرف على مدى قدرة أعضاء النقابة في التأثير على الإدارة وعلى كيفية اختيار أعضاء المكتب النقابي، كذلك التعرف على دورها في تحسين أداء العاملين في دائرة تبغ جبلة. ولقد تمّ إعداد استبانة وتوزيعها على عينة البحث التي بلغت (77) عامل توزّعوا بين (15) عضو في المكتب النقابي و(62) منتسب إلى النقابة. وتمّ تحليل البيانات باستخدام البرنامج الإحصائي SPSS. ولقد توصلت الدراسة إلى مجموعة من النتائج كان من أهمها: . توجد علاقة قوية وطردية بين آلية عمل نقابة التبغ وأداء العاملين، فكلما قامت النقابة بعملها بتوفير الخدمات الضرورية بشكل جيد كلما أدى ذلك إلى تحسين أداء العاملين. . توجد علاقة ذات دلالة احصائية بين آلية عمل نقابة التبغ من الجانب الاقتصادي والترفيهي وبين دورها في تحسين أداء العاملين. . توجد علاقة ذات دلالة احصائية بين آلية عمل نقابة التبغ من الجانب الصحي ودورها في تحسين أداء العاملين. . لا توجد علاقة ذات دلالة احصائية بين قدرة أعضاء النقابة التأثير على الادارة وبين تحسين أداء العاملين. . توجد علاقة ذات دلالة احصائية بين آلية عمل نقابة التبغ من جانب اختيار أعضاء المكتب النقابي ودورها في تحسين أداء العاملين. . عدم قيام النقابة بدورها بالشكل الجيد الذي يحظى برضا أعضائها من الجانبين الاقتصادي والترفيهي، والجانب الصحي، بالإضافة إلى عدم رضا العاملين الأعضاء في النقابة عن دور نقابتهم في تحسين أدائهم.